Evaluation Of Permanent Deformation On Uphill And Downhill Section Of Simpang Ampek - Sasak Road In Pasaman Barat - Mutthmainah; Usrina, Nura; Savira , Nanda Ersa; Fithra, Herman; Mulia , Fenny Artha (Yayasan Meira Visi Persada, 2025)
Roads are a transportation facility that is used by most people. If the road is damaged, it will disturb road users and make them feel uncomfortable when driving. This research method uses the Bina Marga method which determines the average daily traffic and axle load of vehicles that affect road damage on the uphill and downhill sections of the Simpang Ampeik-Sasak road section, West Pasaman Regency, comparing the average daily traffic figures with the determination of the figures according to the class and function of the road. Based on the calculation of the average daily traffic on the uphill and downhill sections, the values exceed the average daily traffic determination in passenger car units, which are worth 2,127 LHR in SMP on the uphill and 2,102 LHR in SMP on the downhill. Regarding the axle load obtained on the road section, vehicles are classified as 6a and 6b, indicating that the road exceeds the truck factor figure, namely 3,583 where the magnitude is 1. The Simpang Ampeik - Sasak road section in West Pasaman Regency experienced an overload, where the type of damage on the ascent and descent is corrugated.